The Role of Virtual Histology Intravascular Ultrasound in the Identification of Coronary Artery Plaque Vulnerability in Acute Coronary Syndromes. Issue 6 (November 2016) - Sinclair, Hannah; Veerasamy, Murugapathy; Bourantas, Christos; Egred, Mohaned; Nair, Anuja; Calvert, Patrick A.; Brugaletta, Salvatore; Mintz, Gary S.; Kunadian, Vijay
Abstract : Markers of coronary plaque vulnerability, such as a high lipid burden, increased inflammatory activity, and a thin fibrous cap, have been identified in histological studies. In vivo, grayscale intravascular ultrasound (IVUS) provides more in-depth information on coronary artery plaque burden than conventional angiography but is unable to accurately distinguish between noncalcific tissue types within the plaque. An analysis of IVUS radiofrequency backscatter based on spectral pattern recognition, such as virtual histology IVUS, allows detailed scrutiny of plaque composition and classification of coronary lesions. This review discusses the virtual histology IVUS technology and its accuracy in identifying vulnerable plaque features, focusing on its use in predicting patient outcomes after acute coronary syndrome, and its limitations in clinical practice.